Darkening of the Greenland Ice Sheet: Fungal Abundance and Diversity Are Associated With Algal Bloom - Perini, Laura; Gostinčar, Cene; Anesio, Alexandre Magno; Williamson, Christopher; Tranter, Martyn; Gunde-Cimerman, Nina (Frontiers in Microbiology, 2019)
Recent studies have highlighted the importance of ice-algal blooms in driving darkening and therefore surface melt of the Greenland Ice Sheet (GrIS). However, the contribution of fungal and bacterial communities to this microbially-driven albedo reduction remains unconstrained. To address this significant knowledge gap, fungi were isolated from key GrIS surface habitats (surface ice containing varying abundance of ice algae, supraglacial water, cryoconite holes, and snow), and a combination of cultivation and sequencing methods utilized to characterize the algal-associated fungal and bacterial diversity and abundance. 697 taxa of fungi were obtained by amplicon sequencing and more than 200 fungal cultures belonging to 46 different species were isolated through cultivation approaches. Basidiomycota dominated in surface ice and water samples, and Ascomycota in snow samples. Amplicon sequencing revealed that bacteria were characterized by a higher diversity (883 taxa detected). Results from cultivation as well as ergosterol analyses suggested that surface ice dominated by ice algae and cryoconite holes supported the highest fungal biomass (104 – 105 CFU/100 mL) and that many fungal taxa recognized as endophytes and plant pathogens were associated with dark ice characterized by a high abundance of ice algae. This paper significantly advances this field of research by investigating for the first time the fungal abundance and diversity associated with algal blooms causing the darkening of the GrIS.